Determining Baltic salmon foraging areas at sea using stable isotopes in scales—a tool for understanding health syndromes. (14th December 2021) - Jones, Douglas; Dahlgren, Elin; Jacobson, Philip; Karlson, Agnes M L
Abstract: Managing fish stocks for species migrating between freshwater and the sea is challenging when ecological information for life stages at sea is poorly known. Oceans offer increased opportunity for growth but also morbidity and mortality. By improving our understanding of foraging at sea we can better identify factors driving stock health and recruitment. We analysed stable isotopes of carbon and nitrogen (δ 13 C and δ 15 N) in scales from tagged Baltic salmon ( Salmo salar ) caught at sea over four decades. We found consistently divergent patterns in δ 13 C and δ 15 N between the two main basins of the Baltic Sea, which can be used to determine foraging area. Isotope analysis of amino acids revealed differences in source δ 15 N as the main reason for observed differences between basins. We also analysed isotopes in scales and thiamin concentrations in roe (thiamin deficiency can cause substantial fry mortality) from adult female salmon returning to a river to spawn in 2017 and 2018. Individuals with low thiamin levels were associated with offshore feeding in both basins, suggesting the deficiency syndrome is widespread in the Baltic Sea.